The Cultural Reconstruction of Traditional "Filial Piety" in the Context of Smart Elderly Care - Fu, Shiying (Education Insights, 2026)
This study aims to systematically explore the reconstruction and transformation of traditional "filial piety" culture within the rapidly evolving context of smart elderly care. With unprecedented technological advancements and profound changes in global demographic and social structures, traditional filial piety culture faces significant new challenges, alongside unique opportunities for modernization. The research first comprehensively reviews the historical evolution of filial piety culture—tracing its trajectory from ancient times through modern periods to its current state under contemporary smart elderly care trends—carefully analyzing critical shifts in its core connotations and practical extensions. Subsequently, it provides an in-depth overview of smart elderly care, covering technology-driven transformations in caregiving approaches, the distinct advantages and inherent limitations of intelligent elderly care services, and their future development prospects in an aging society. Building upon this robust theoretical foundation, the study focuses on the fundamental redefinition of filial piety culture within smart elderly care frameworks. This includes the crucial paradigm shift from mere material support to profound emotional care, the integration of innovative communication methods utilizing digital technology among family members, and the establishment of new, adaptive behavioral norms for fulfilling filial duties. Additionally, the paper offers profound philosophical reflections on the ongoing transformation of filial piety culture. It critically examines its complex relationships from both individualist and collectivist perspectives, evaluates the intrinsic connection between quality of life and fundamental human dignity, and delineates the evolving boundaries between ethical moral responsibilities and formal legal obligations.